Strategi Penghidupan Peternak Sapi Perah Di Lereng Selatan Gunungapi Merapi Pasca Erupsi 2010 - Siti Andarwati; R Rijanta; Rini Widiati; Yanin Opatpatanakit (Buletin Peternakan, 2017)
This study aims to analyzed the strategies of dairy farmers in disaster prone areas (DPA) in the southern slopes of  Merapi  for sustaining livelihood after the eruption of Merapi volcano in 2010. Research conducted by the Survey method. Sampling was done by using the Census methods, consists of 84 dairy farmers in DPA III (Kaliadem hamlet) and 50 dairy farmers in DPA II (Gondang Wetan hamlet). Both hamlets were including Cangkringan district To find out the farmers strategies used descriptive method, that was to gather as much information related to their livelihood, covers three important aspects: assets (livelihood resources), access and activity. Statistical analysis that used for classification of livelihood strategies was Factor Analysis with SPSS 18. The results showed, there were nine  strategy chosen by the dairy farmers for sustaining livelihoods in order to ensure sustainable livelihoods: The combination of financial, physical asset and natural resources utilization, as well as maintained dairy farm; The combination of physical and social capital utilization, social access and business diversification; Utilization of social access; Utilization of social help and mutual access, Utilization of liquid assets and social capital; The combination of psychological factors with utilization of financial & social access; Utilization of financial assets and access with the use of pause time; Utilization of social capital; and Farm diversification. The combination of financial, physical asset and natural resources utilization, as well as maintained dairy farm was the most of dominant strategy chosen by the farmers, with the greatest cumulative value (27.645%). Psychological variable (sense of security) was to be the new finding in the theory of sustainable livelihood strategies. Social capital was the variable that dominated the basic options of sustainable livelihood strategy of dairy farmers after the eruption of Merapi in 2010.